Pengaruh Brand Image dan Influencer Marketing terhadap Keputusan Pembelian Konsumen melalui Minat Beli sebagai Variabel Intervening: Studi pada Followers Akun TikTok @Skintific_id - Nabila, Jihan; Azijah, Nur (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The sales increase of Skintific products decreases in the April period and increases in the July period in 2022, and continues to increase from year to year. Influencer marketing can also be used as an appropriate marketing strategy to increase sales results and promote products widely. This is because influencers have the ability to give the public confidence in the image of a product, so with this ability it is able to influence the purchase decision of a particular product by customers. The purpose of this study is to determine